2013
DOI: 10.1097/ta.0b013e3182858a3e
|View full text |Cite|
|
Sign up to set email alerts
|

Lactate clearance as a predictor of mortality in trauma patients

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
135
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 19 publications
13
135
1
7
Order By: Relevance
“…Changes in lactate concentrations have been shown to provide an early and objective evaluation of a patient's response to therapy and repeated lactate determinations have proved to be a reliable prognostic index for patients with hemorrhagic shock. 20 Early return of lactate levels to normal levels (<2 mmol/l) within 24 h has been proved to be associated with improved outcomes in terms of mortality. A significant correlation has been established between the admission base deficit and transfusion requirements within the first 24 h and the risk of post-traumatic organ failure or death.…”
Section: Shock-hypoperfusionmentioning
confidence: 99%
“…Changes in lactate concentrations have been shown to provide an early and objective evaluation of a patient's response to therapy and repeated lactate determinations have proved to be a reliable prognostic index for patients with hemorrhagic shock. 20 Early return of lactate levels to normal levels (<2 mmol/l) within 24 h has been proved to be associated with improved outcomes in terms of mortality. A significant correlation has been established between the admission base deficit and transfusion requirements within the first 24 h and the risk of post-traumatic organ failure or death.…”
Section: Shock-hypoperfusionmentioning
confidence: 99%
“…With regard to lactate, Odom et al reported admission lactate to be a potent predictor of mortality, independently of a host of confounders. 2 A lactate level of >4mmol/l increased the odds of death by a factor of 3.8, compared with those with a lactate level of <2.5mol/l. This was in spite of adjustment for age, injury severity score (ISS), Glasgow coma scale (GCS) score, heart rate and blood pressure.…”
mentioning
confidence: 99%
“…(18,19) They are also associated with mortality and morbidity in elderly with and without infections. (20) This study has additional limitations.…”
Section: Discussionmentioning
confidence: 99%